EFEKTIVITAS PEMBELAJARAN DARING PADA MATA PELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI MATERI MICROSOFT WORD - Muniroh Muniroh (Akademika : Jurnal Teknologi Pendidikan, 2021)
Learning during a pandemic requires online and offline learning. In the subject of information and communication technology (ICT) students are less understood. This is due to the reduced hours of subjects and the absence of activities in the computer lab. This study aims to determine the effectiveness of online learning on learning outcomes of information and communication technology (ICT) subjects in class VIII Microsoft Word material. The method used is observation and experiment using pretest and posttest. The sample of this research is 73 students which are divided into control class and experimental class. The approach used is descriptive quantitative, namely calculating the effect size of learning outcomes by identifying the mean, maximum and minimum values ​​and calculating the t-test. The results of the analysis that has been carried out on the control and experimental classes that the nGain score test shows the average value for the experimental class (online) is 49.9537 or 50% is included in the less effective category. While the average value for the control class (offline) which is 60.8108 or 60.8% is included in the quite effective category. So it can be concluded that online learning is less effective in improving MS skills. Words. While the use of offline learning is quite effective.